Three-dimensional potential and electric field distributions in HV cable insulation containing multiple cavities - Afrouzi, Hadi Nabipour (2013)
Cross-linked polyethylene is widely used as electrical insulation because of its excellent electrical properties such as low dielectric constant, low dielectric loss and also due to its excellent chemical resistance and mechanical flexibility. Nevertheless, the most important reason for failure of high voltage equipment is due to its insulation failure. The electrical properties of an insulator are affected by the presence of cavities within the insulating material, in particular with regard to the electric field and potential distributions. In this paper, the electric field and potential distributions in high voltage cables containing single and multiple cavities are studied. Three different insulating media, namely PE, XLPE, and PVC was modeled. COMSOL software which utilises the finite element method (FEM) was used to carry out the simulation. An 11kV underground cable was modeled in3D for better observation and analyses of the generated voltage and field distributions. The results show that the electric field is affected by the presence of cavities in the insulation. Furthermore, the field strength and uniformity are also affected by whether cavities are radially or axially aligned, as well as the type of the insulating solid. The effect of insulator type due the presence of cavities was seen most prevalent in PVC followed by PE and then XLPE.